César Vallejo's magnetic poetry - Martos Carrera, Marco (2014)
The article reviews all the literary career of César Vallejo in the field of poetry. It also revises his relationship with modernism and points out how he became the standard-bearer at the forefront of the Spanish language up to reach the deepest originality in Latin American tradition.